2012
DOI: 10.1590/s0100-69912012000600003
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonina como biomarcador de prognóstico da sepse grave e choque séptico

Abstract: OBJETIVO: Avaliar a tendência da concentração plasmática e do clearance de procalcitonina (PCT-c) como biomarcadores de prognóstico de pacientes com sepse grave e choque séptico, comparado a um outro marcador precoce de prognóstico representado pelo número de critérios de SIRS no momento do diagnóstico da sepse. MÉTODOS: Estudo de coorte prospectivo observacional onde foram incluídos pacientes com sepse grave e choque séptico. A concentração sérica de procalcitonina foi determinada no momento do diagnóstico da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
1
14
0
2
Order By: Relevance
“…In 28 patients with severe sepsis/septic shock from Brazil, Azevedo et al . [ 14 ] found that the procalcitonin level after 24–48 h was significantly different among survivors and NS (median 8.2 ng/ml vs. 68.6 ng/ml at 24 h and 4.6 ng/ml and 31 ng/ml at 48 h among survivors and NS respectively). Similar findings were obtained by Suberviola et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 28 patients with severe sepsis/septic shock from Brazil, Azevedo et al . [ 14 ] found that the procalcitonin level after 24–48 h was significantly different among survivors and NS (median 8.2 ng/ml vs. 68.6 ng/ml at 24 h and 4.6 ng/ml and 31 ng/ml at 48 h among survivors and NS respectively). Similar findings were obtained by Suberviola et al .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in 28 patients with severe sepsis/septic shock, Azevedo et al . [ 14 ] found procalcitonin clearance at 24 h was significantly higher among survivors as compared to NS ( P = 0.028). Suberviola et al .…”
Section: Discussionmentioning
confidence: 99%
“…in infant populations. [1920] Azevedo et al . showed a higher level of procalcitonin in sepsis and severe sepsis in adult patients were related to increase risk mortality.…”
Section: Discussionmentioning
confidence: 99%
“…showed a higher level of procalcitonin in sepsis and severe sepsis in adult patients were related to increase risk mortality. [19] In the neonatus population, the level of procalcitonin can be used as a marker for early detection of sepsis in the intensive care unit. [2120] As a sepsis marker in the neonatus, procalcitonin is better than C-Reactive Protein (CRP);[21] however, CRP can be used as a marker for bacterial co-infection in the viral-induced bronchiolitis infant populations.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers suggested that serial lactate and ProCT measurements may be used together to enhance the results (Phua et al, 2008). Other studies showed that ProCT is elevated in patients with sepsis, which qualified ProCT as an acceptable biomarker (Azevedo et al, 2012;Becker, Snider, & Nylen, 2010;Kibe, Adams, & Barlow, 2011;McLean, Tang, & Huang, 2015;Riedel, 2012). Shapiro et al (2009) defined a panel of biomarkers consisting of neutrophil gelatinase-associated lipocalin, interleukin-1ra, and Protein C. This panel of biomarkers was a good predictor of severe sepsis, septic shock, and death of patients with suspected sepsis in Emergency Departments (Shapiro et al, 2009).…”
Section: Septic Shock Biomarkersmentioning
confidence: 99%